2018
DOI: 10.1021/acs.jpcc.8b02684
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Analysis of Catalytic and Oxygen Interfacial Transfer Effects on MnO2 Deposited on Gold Electrodes

Abstract: A theoretical model for obtaining thermochemical and kinetic information on oxygen interfacial transfer in metal oxides deposited on gold electrodes, based in the voltammetry of immobilized particle methodology, is presented. It is applied to MnO2 microparticulate deposits on gold in contact with aqueous NaOH solution using the voltammetric signals for the oxidation of gold to gold oxide monolayer and its subsequent desorptive reduction. Assuming reversibility, voltammetric peak potentials permit to estimate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 55 publications
(79 reference statements)
1
5
0
Order By: Relevance
“…This experimental fact is in accordance with the initial reaction rates calculated for these catalysts as shown below. Interestingly, a control reaction in the absence of oxygen showed the existence of a residual oxidation activity by the [Ru]-K-OMS2 (2 wt%) catalyst suggesting the plausible involvement of a Mars van Krevelen mechanism, according to which the structural lattice oxygen would participate in the reaction being later reoxidized by molecular oxygen when present (entry 3, Table 2) [15,16] as it has been already pointed out for related octahedral molecular sieves [17][18][19]55]. The catalytic activity of RuO x /K-OMS2 (1 wt%) and K-OMS2 was also studied under inert atmosphere just for comparison and we observed that the extension of benzylic alcohol oxidation was greater for the isomorphically substituted catalyst [Ru]-K-OMS2 (2 wt%) than for catalysts RuO x /K-OMS2 (1 wt%) and K-OMS2 (compare entries 3, 5 and 8 in Table 2).…”
Section: Besides the Remarkable Difference Of Tof Values Obtained With [Ru]-k-oms2 (2 Wt%)mentioning
confidence: 69%
See 2 more Smart Citations
“…This experimental fact is in accordance with the initial reaction rates calculated for these catalysts as shown below. Interestingly, a control reaction in the absence of oxygen showed the existence of a residual oxidation activity by the [Ru]-K-OMS2 (2 wt%) catalyst suggesting the plausible involvement of a Mars van Krevelen mechanism, according to which the structural lattice oxygen would participate in the reaction being later reoxidized by molecular oxygen when present (entry 3, Table 2) [15,16] as it has been already pointed out for related octahedral molecular sieves [17][18][19]55]. The catalytic activity of RuO x /K-OMS2 (1 wt%) and K-OMS2 was also studied under inert atmosphere just for comparison and we observed that the extension of benzylic alcohol oxidation was greater for the isomorphically substituted catalyst [Ru]-K-OMS2 (2 wt%) than for catalysts RuO x /K-OMS2 (1 wt%) and K-OMS2 (compare entries 3, 5 and 8 in Table 2).…”
Section: Besides the Remarkable Difference Of Tof Values Obtained With [Ru]-k-oms2 (2 Wt%)mentioning
confidence: 69%
“…To this respect it is important to indicate that the oxidation of alcohols to aldehydes has been extensivelly studied in the presence of manganese molecular sieves [18,19,[53][54][55] as well as ruthenium catalysts although separately [56][57][58]. In general, stoichiometric amounts of high valent metal oxidants have been traditionally used to accomplish this transformation, but they have high toxicity and negative economic implications [59].…”
Section: Catalytic Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most critical assumptions of the Scholz model is that the reaction starts at the three-boundary, which has been widely observed and used to explain electrochemical processes in solid-state materials, e.g., metal oxides. The first observation of the three-phase boundary was demonstrated by Scholz et al through the reduction of lead oxide to lead. In situ atomic force microscopy was applied to monitor the real-time reduction of a single α-PbO particle (Figure a) .…”
Section: Scholz Modelmentioning
confidence: 99%
“…Doping processes are clearly used to tune the structure, morphology and lattice parameters in order to provide novel chemical and physical properties to the solid. In this line, structural defects, active metal species derived from doping [136][137][138] and oxygen vacancies [105,139,140], together with unexpected synergic effects [132,141], will define the true performance of the materials in catalytic reactions.…”
Section: Assessment Of Doping Processesmentioning
confidence: 99%